2008
DOI: 10.1002/hipo.20501
|View full text |Cite
|
Sign up to set email alerts
|

Computation by oscillations: Implications of experimental data for theoretical models of grid cells

Abstract: ABSTRACT:Recordings in awake, behaving animals demonstrate that cells in medial entorhinal cortex (mEC) show ''grid cell'' firing activity when a rat explores an open environment. Intracellular recording in slices from different positions along the dorsal to ventral axis show differences in intrinsic properties such as subthreshold membrane potential oscillations (MPO), resonant frequency, and the presence of the hyperpolarization-activated cation current (h-current). The differences in intrinsic properties co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
107
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(120 citation statements)
references
References 73 publications
13
107
0
Order By: Relevance
“…This model provides an alternate implementation of the oscillatory interference model Burgess, 2008) that is compared to the implementation using membrane potential oscillations Hasselmo et al, 2007;Giocomo and Hasselmo, 2008a).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This model provides an alternate implementation of the oscillatory interference model Burgess, 2008) that is compared to the implementation using membrane potential oscillations Hasselmo et al, 2007;Giocomo and Hasselmo, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous modeling showed that membrane potential oscillations in entorhinal neurons might also contribute to grid cell firing Giocomo et al, 2007;Hasselmo et al, 2007;Giocomo and Hasselmo, 2008a). Entorhinal Layer II stellate cells show subthreshold membrane potential oscillations when depolarized near firing threshold (Alonso and Llinas, 1989;Alonso and Klink, 1993;Giocomo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations